Tipologia de conflitos de usos das águas: estudos de casos no estado do Ceará - Pinheiro, Maria Inês Teixeira (2002)
Water, which is critical for life, has caused conflicts and disputes for thousands of years. Water shortage has exacerbated over the last years, in particular in semiarid regions, and brought many concerns, as it may increase the conflicts among water users. This study formulates a typology of conflicts based on a sample selected in the State of Ceará. This typology may serve as an instrument to support the decision makers and stakeholders in the settlement of conflicts associated with water use. Conflicts are analyzed according to some characteristics, such as: duration, involved parties, affected area, purpose, description, time, referenced legal instrument, environmental impact, mediating institutions. History and current status of conflicts are also addressed. After the systematization, analysis and discussion of information and formulation of typology, some conclusions were drawn, with emphasis the influence of the hydrological scenario on the length of the conflict, the more active involvement of classes of isolated or grouped individuals, the proportionality between punctual and systemic conflicts, the great incidence of conflicts in the water resource control area, the historical importance of the problem, the need of a greater attention of managers to the organization of users, and deeper hydrological understanding of basins toward preventing conflicts by means of dialogues and previous negotiations.